Esthetic Crown Lengthening with Ostectomy for The Correc-tion of Gummy Smile: A Case Report - Dik Megaputri Handayani; Eka Pramudita Ramadhany; I Gede Krisna Merta Yoga (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Short clinical crowns may lead to esthetic concerns, particularly excessive gingival display (gummy smile). Case: A 25-year-old female presented with a chief complaint of short teeth and excessive gingival display during smiling. Clinical examination revealed a gingival display of more than 2 mm, with no signs of periodontal inflammation and adequate keratinized gingiva. The diagnosis was excessive gingival display due to altered passive eruption type IB in the region of teeth 15–25. Case Management: Crown lengthening with a full-thickness flap and ostectomy was performed. Follow-up evaluations up to one month demonstrated favorable healing, patient satisfaction, no spontaneous bleeding or periodontal pocket formation, and stable treatment outcomes. Discussion: Accurate identification of altered passive eruption and appropriate management of the supracrestal tissue attachment are critical for successful esthetic crown lengthening. In this case, osseous resection was necessary to establish adequate periodontal dimensions and achieve stable esthetic outcomes. Conclusion: Crown lengthening with ostectomy is an effective and predictable treatment modality for altered passive eruption type IB.